Can nascent soot particles burn from the inside?. (November 2016) - Grančič, Peter; Martin, Jacob W.; Chen, Dongping; Mosbach, Sebastian; Kraft, Markus
Abstract: The trajectories of a single nitrogen molecule resulting from a series of collisions with coronene molecular clusters of varying size are determined numerically by means of classical molecular dynamics simulations at two system temperatures, corresponding to the clusters being in solid and liquid state. The observed bimodality of the residence time distributions that corresponds to a combination of specular and diffuse molecular scattering tends to disappear with increasing temperature due to the more rapid rearrangements of the coronene cluster constituent molecules in the liquid state. The mean residence time decreases with increasing system temperature and appears to be independent of the coronene cluster size within the cluster size-range considered here. The recorded trajectories of the nitrogen probe are relatively tortuous, on average one order of magnitude longer than the shortest path connecting the impact and desorption points. The vast majority of the sites visited during the nitrogen molecule residence period correspond to the atoms at the edge of coronene molecules, mainly hydrogens. The intermolecular cohesive forces between the molecules cause that the coronene clusters are impenetrable by the nitrogen probe at temperatures below their thermal dissociation point.